2016
DOI: 10.3390/app6030066
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Hot Compressive Deformation Behavior for Superalloy Nimonic 80A by BP-ANN Model

Abstract: Abstract:In order to predict hot deformation behavior of superalloy nimonic 80A, a back-propagational artificial neural network (BP-ANN) and strain-dependent Arrhenius-type model were established based on the experimental data from isothermal compression tests on a Gleeble-3500 thermo-mechanical simulator at temperatures ranging of 1050-1250˝C, strain rates ranging of 0.01-10.0 s´1. A comparison on a BP-ANN model and modified Arrhenius-type constitutive equation has been implemented in terms of statistical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…As one can see in Figure 5, the values of A 3 , n 2 , α, and Q 3 constants are significantly dependent on true strain due to changes in the microstructure during deformation. To include the strain (ε) influence too, the constitutive Equation (3) was modified by using fourth-degree polynomial dependence of the material constants [28,29] As one can see in Figure 6a, the average difference between calculated and experimental flow stress values is 3.3%. In addition, the accuracy of the constitutive model was checked by the modeling of the samples' compression at a strain rate of 1 s −1 using the FEM method.…”
Section: Constitutive Model Of Hot Deformation Behaviormentioning
confidence: 99%
“…As one can see in Figure 5, the values of A 3 , n 2 , α, and Q 3 constants are significantly dependent on true strain due to changes in the microstructure during deformation. To include the strain (ε) influence too, the constitutive Equation (3) was modified by using fourth-degree polynomial dependence of the material constants [28,29] As one can see in Figure 6a, the average difference between calculated and experimental flow stress values is 3.3%. In addition, the accuracy of the constitutive model was checked by the modeling of the samples' compression at a strain rate of 1 s −1 using the FEM method.…”
Section: Constitutive Model Of Hot Deformation Behaviormentioning
confidence: 99%
“…The progress in neural networks has greatly stimulated research. Studies [24] have reported the automatic classification systems of defects, elimination of the adverse effects of environmental parameters in capacitive pressure sensors [25], and pattern recognition for pipeline leakage localization systems [26]. Neural networks trained by certain samples can process enormous amounts of data and recognize the patterns of test samples in a short period.…”
Section: Introductionmentioning
confidence: 99%
“…It is chemically a complex superalloy whose main components of the alloying elements are Cr, Mo, W, Ti, Ta, Al. Nimonic 80A alloys are commonly used in jet engine, gas turbine because of their high creep strength, oxidation resistance and strong resistance to high temperature corrosion [1][2][3]. It is known that some materials have higher hardness as they deform plastically.…”
Section: Introductionmentioning
confidence: 99%